Does Trust Mediate Job Satisfaction Factor and Intention Factor to Keep on among the IT Employees? - Kiruba, Angelin S.; Jenifer, S. Clemence; Drewitt, Christine; Suraj, P. G. (International Review of Management and Marketing, 2026)
“Intention to stay with the organization befalls when a person’s work nature, responsibilities, environment and the benefits are in line with his/her expectations. This sense of balance might be a product of several influences like Job satisfaction, trust among the coworkers, respectable performance of the organization and much more.” Though he is bestowed with various amenities and welfare measure, low scores on these factors can induce the employees to leave the organization. Understanding the factors which impacts the intention of the employees to in the organization is vital because it will improve the productivity of the organization as the whole. The project aims at measuring loyalty of the IT and ITES employees. This study was undertaken to identify the factors influencing intention of Employees to remain in the organization. Descriptive research design is used for this project. Primary data was collected through Questionnaire. The statistical tools used were Regression, Correlation, Chi-Square and ANOVA. The variables were grouped into factors namely Job Satisfaction, Organization Performance and Trust among colleagues. The current study resulted that Trust partially mediates linking the relationship of Job Satisfaction and Intention to keep on. Few suggestions were drawn and presented to the companies to improve the Intention of Employees to stay.